ENHANCEMENT OF PORTLAND CEMENT CLINKER ACTIVITY USING INDUSTRIAL WASTE INCLUDING GYPSUM - Jovliyev Ziyodulla (Galaxy International Interdisciplinary Research Journal, 2022)
Decree of the President of the Republic of Uzbekistan No. PF-4947 of February 7, 2017 "On the Strategy of Actions for Further Development of the Republic of Uzbekistan", No. PQ-2615 of September 28, 2016 "Construction in 2016-2020 further development of the industryon the program of measures", PQ-3182 of August 8, 2017 "On priority measures to ensure rapid socio-economic development of the regions", PQ-4335 of May 23, 2019 No. "Addendum on the rapid development of the construction materials industryDecisions on measures" have been adopted, and the construction materials production industry is developing widely in our country.[1]One of the most promising directions in the use of industrial waste is its use as a building material in production. It meets 40% of the demand for raw materials.